IMPLEMENTASI PEMBELAJARAN SECARA DARING DI SEKOLAH DASAR ERA PANDEMI COVID-19 - Saleh, Chairul (Fakultas Ilmu Pendidikan, 2021)
This study aims to describe the implementation of online learning, as well as identify the supporting factors and inhibiting factors for online learning in the era of the COVID-19 pandemic at SD Negeri Samirono. The research method is descriptive with a qualitative approach. The research subjects were principals, committees, schools, teachers, guardians of students and students. Data collection techniques are observation, interviews, and documentation. The data analysis technique uses the theory of Miles, Huberman Saldana. The validity of the data used triangulation of sources and techniques. The results of the study show 1) Implementation of online learning in the era of the covid-19 pandemic at SD Negeri Samirono, seen from the aspects of (a) Communication, verbally and in the media, (b) Human resources for all components involved in implementing policies in schools, financial resources from government assistance in the form of study quotas, resources for laptops and wi-fi availability in schools, (c) Disposition, ready and committed, (d) The bureaucratic structure adjusts to the school's organizational structure. 2) Supporting Factors (a) high teacher commitment (b) quota assistance, (c) adequate school infrastructure, (d) flexible online learning. 3) Inhibiting factors (a) Inadequate student infrastructure, (b) limited quota assistance, (c) students find it difficult to understand lessons, (d) students are late in submitting assignments, (e) lack of parental assistance.